Memórias da diversidade na Paraíba: as dores e os guardins de Nina Kelly - Ferro, Sérgio Pessoa (2019)
This work tells the Nina Kelly’s life story, fifty-nine years old, transvestite, transformista, seamstress, highlight of samba school. Born in the interior fromParaíba, she migrated still adolescent to capital, where she settled down. The narrative was constructed based on an interdisciplinary methodology, choosing the textual genre of the interview commented as a method of discursive production. We position human rights studies between literary theory, history, geography, psychology, and law. As primary sources of information, we manage, in addition to the semi-structured interview, photographs, videos and memorabilia that make up the personal collection of the subject. The perspective of Maurice Halbwachs offers us the concept of memory as a social construction, so that the individual and the collective intersect in our memories. Thus, through the reminiscences of Nina, we intend to delve into the social memory of the dissenting sex-gender community from João Pessoa.